Tissue Engineering - Hauser, Hansjörg; Fussenegger, Martin M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
Over the past decade, tissue engineering has spread in importance in fields as distinct as biotechnology, biopharmaceutical manufacturing, chemical engineering, cell biology, developmental biology, gene therapy, medical sciences and organic chemistry. In Tissue Engineering, 2nd Edition, a team of experts from these various disciplines share recent advances in tissue engineering-related methodologies in order to provide a comprehensive volume that integrates a wide spectrum of methods. Written in the format of the highly successful Methods in Molecular Medicine™ series, each chapter seeks to drive tissue engineering into a clinical reality with step-by-step laboratory protocols, lists of necessary materials, and tips on troubleshooting and avoiding known pitfalls. Thorough and timely, Tissue Engineering, 2nd Edition is an invaluable resource for all scientists leading the way toward the first successful implantation of a fully functional artificial organ.
In Vitro Expansion of Tissue Cells by Conditional Proliferation -- Stem Cell Engineering Using Transducible Cre Recombinase -- Human Embryonic Stem Cells for Tissue Engineering -- Culture and Characterization of Human Bone Marrow Mesenchymal Stem Cells -- Skeletal (“Mesenchymal”) Stem Cells for Tissue Engineering -- Biomaterials/Scaffolds -- Synthetic Hydrogel Matrices for Guided Bladder Tissue Regeneration -- Generation of Multicellular Tumor Spheroids by the Hanging-Drop Method -- In Vitro Vascularization of Human Connective Microtissues -- Artificial Skin -- Small Blood Vessel Engineering -- Artificial Pancreas to Treat Type 1 Diabetes Mellitus -- Human Articular Chondrocytes Culture -- Cardiomyocytes From Human and Mouse Embryonic Stem Cells -- Myocardial Restoration and Tissue Engineering of Heart Structures -- Practical Aspects of Cardiac Tissue Engineering With Electrical Stimulation -- Biological Scaffolds for Heart Valve Tissue Engineering -- In Vitro Heart Valve Tissue Engineering.
Keywords: Biotechnology; Biomaterials; Human genetics; Cell biology; Biotechnology; Biomaterials; Human Genetics; Cell Biology